Stone Formation on Suture Material Following Laparoscopic Pyeloplasty Causing Recurrent Puj Obstruction: A Case Report - Uddin, Md Nasir; Hasan, MM; Kakan, Fahmida Bayes; Khan, Sarwar Hossain (Bangladesh Journal of Urology, 2020)
Male patient 46 years of age presented with history of Laparoscopic A-H pyeloplasty with DJ stenting for left side hydronephrosis due to PUJ obstruction. After stent removed he experienced intermittent flank pain, discomfort with fullness sensation. On examination there was mild left renal angle tenderness. Urinalysis showed RBC. USG revealed moderate left hydronephrosis. CT urogram showed left side gross HDN with 5 mm PUJ stone. Tc-99m DTPA renal scan revealed partial obstruction. After counseled and exploration founded an impacted PUJ stone. During removal of PUJ stone, identified a suture material embedded by the stone. After removed the stone,PUJ still narrowed. Then A- H pyeloplasty done with placed a D-J stent in situ. The patient had a good post-operative recovery. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.164-165